Analisis Kinerja Keuangan dengan Pendekatan Metode RGEC (Risk Profile, Good Corporate Governance, Earnings, Capital) pada Unit Usaha Syariah Bank Kaltimtara - Mat Juri; Ibrahim Musa; Sulfiana Sulfiana (Politeknik Negeri Samarinda, 2022)
The purpose of this study was to analyze the financial performance of the BPD Kaltimtara Syariah for the 2014-2018 period using the RGEC method approach (Risk Profile, Good Corporate Governance, Earnings, Capital). The analytical tool used is the RGEC method (Risk Profile, Good Corporate Governance, Earnings, Capital), while the research method uses descriptive quantitative approach. The object of this research is the East Kalimantan Regional Development Bank registered in the Bank Indonesia directory, which has annual reports from 2014 to 2018. Data collection techniques used are documentation techniques and library techniques. The results showed the overall financial performance of BPD Kaltimtara Syariah during the 2014-2018 period in terms of risk profile, namely by analyzing credit risk represented by the ratio of NPF (Non Performing Finance) said to be quite good and from liquidity risk analysis represented by FDR ratio (Finance to Deposit Ratio) can be said to be quite liquid. While in terms of GCG (Good Corporate Governance) the Bank's performance is good and overall financial performance in terms of earnings (earnings) is by analyzing the ROA (Return On Assets) or profit based on assets and the ratio of NIM (Net Interest Margin) or management capability in controlling Bank costs are said to be good and the BOPO ratio (Operational Costs at Operational Income) is said to be less efficient in processing profits. Overall financial performance in terms of capital by analyzing the ratio of capital to ATMR (Risk Weighted Assets) represented by calculating the ratio The Bank's CAR (Capital Adequacy Ratio) is said to be very good.